Celestial strings: Field theory, conformally soft limits, and mapping the worldsheet onto the celestial sphere - Castiblanco, Lina (2024)
We compute the celestial correlators corresponding to tree-level 5-gluon amplitudes in the type I superstring theory. Since celestial correlation functions are obtained by integrating over the full range of energies, there is no obvious analog of the ′→0 limit in this basis. This is manifestly shown by a factorization of the ′ dependence in the celestial string amplitudes. Consequently, the question arises as to how the field theory limit is recovered from string theory in the celestial basis. This problem has been addressed in the literature for the case of 4-gluon amplitudes at tree level, where the forward scattering limit of the stringy factor was identified as a limit in which celestial Yang-Mills 4-point function is recovered. Here, we extend the analysis to the case with five gluons, for which the string moduli space allows for more types of limits, thus allowing us to investigate this aspect in more detail. Based on celestial data only, we study the regime in which one arrives at the correct celestial field theory limit. We also study other properties of the celestial string amplitudes, namely, the conformally soft theorem, effective field theory expansion in the conformal basis, and a map that arises in the regime of high-energy/large-scaling dimension that connects the punctured string world sheet to the insertion of primary operators in the celestial CFT for the massless -point string amplitude.